Elevated sphingosine-1-phosphate lyase leads to increased metabolism and reduced survival in adrenocortical carcinoma. Issue 1 (11th January 2023) - Williams, Jack L; Smith, Chris; Hall, Charlotte; Khaled, Zakaa; Maharaj, Avinaash; Kwong, Ruth; Pittaway, James; Casas, Josefina; Parvanta, Laila; Abdel-Aziz, Tarek Ezzat; Palazzo, Fausto; Chung, Teng-Teng; et al.
Abstract: Objective: Adrenocortical carcinomas (ACCs) are invasive tumours arising in the adrenal cortex, and steroidogenic tumours are associated with worse prognostic outcomes. Loss-of-function mutations in sphingosine-1-phosphate lyase (SGPL1) cause primary adrenal insufficiency and as a key degradative enzyme in the sphingolipid pathway, SGPL1 also influences the balance of pro-proliferative and pro-apoptotic sphingolipids. We, therefore, hypothesized increased SGPL1 may be linked to increased disease severity in ACC. Design: Analyse SGPL1 expression impact on patient survival and adrenal cancer cell phenotype. We analysed two ACC cohorts with survival and corresponding transcriptomic data, focusing on SGPL1 and sphingolipid pathway genes. In vitro, we generated SGPL1-knockout and overexpressing H295R adrenocortical cells to investigate the role of SGPL1 in cell signalling in ACCs. Results: We found increased expression of several sphingolipid pathway receptors and enzymes, most notably SGPL1 correlated with reduced patient survival in both cohorts. Overexpression of SGPL1 in the H295R cell line increased proliferation and migration while reducing apoptosis, while SGPL1 knockout had the opposite effect. RNA-seq revealed a global increase in the expression of genes in the electron transport chain in overexpressing cells, correlating with increased aerobic respiration and glycolysis. Furthermore, the opposite phenotype was seen in cells lacking SGPL1. We subsequently found the increased proliferation is linked to metabolic substrate availability and increased capacity to use different fuel sources, but particularly glucose, in overexpressing cells. Conclusions: We, therefore, propose that SGPL1-overexpressing ACC tumours reduce patient survival by increasing fuel usage for anabolism and energy production to facilitate growth and invasion.